Opowieść o potopie w Księdze Bereszit (6–9) a mit o wylewie oceanu w andyjskim manuskrypcie z Huarochirí (F66R–F66V). Charakterystyka przekazów i analiza paralelizmów - Waszak, Jan (Humaniora. Czasopismo Internetowe, 2025)
Both the Book of Genesis (6–9) and the Andean manuscript of Huarochirí (F66R–F66V) contain flood myths which, despite cultural and religious differences, exhibit numerous parallels. This article endeavors a comparative analysis of both narratives, focusing particularly on their theological, cosmological, and anthropological significance. The research addresses the questions: “How do aquatic motifs reflect universal religious archetypes?” and “What common structural and functional elements can be identified in stories originating from such disparate traditions?” The study considers both the content of the myths and their historical-cultural contexts, exploring themes of destruction, cosmological renewal, and the relationship between the sacred and humanity. The article’s objective is not only to highlight parallels but also to reveal their role within a broader religio-cultural framework.